2015
DOI: 10.1007/s00204-015-1545-2
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variation in gene expression responses and metabolite formation in acetaminophen-exposed primary human hepatocytes

Abstract: Acetaminophen (APAP) is a readily available over-the-counter drug and is one of the most commonly used analgesics/antipyretics worldwide. Large interindividual variation in susceptibility toward APAP-induced liver failure has been reported. However, the exact underlying factors causing this variability in susceptibility are still largely unknown. The aim of this study was to better understand this variability in response to APAP by evaluating interindividual differences in gene expression changes and APAP meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…Previous studies suggested that DMEs were the most important proteins accounting for the inter-individual variability of APAP-induced hepatotoxicity and the development of adaptive tolerance (Adjei et al 2008; Court et al 2001; Jetten et al 2016; McKillop et al 1999; Strubelt et al 1979). Since un-biased gene expression analyses revealed that genes encoding DMEs and NRs were highly dysregulated after APAP treatment, detailed expression profiles of key DMEs involved in the APAP metabolism were examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that DMEs were the most important proteins accounting for the inter-individual variability of APAP-induced hepatotoxicity and the development of adaptive tolerance (Adjei et al 2008; Court et al 2001; Jetten et al 2016; McKillop et al 1999; Strubelt et al 1979). Since un-biased gene expression analyses revealed that genes encoding DMEs and NRs were highly dysregulated after APAP treatment, detailed expression profiles of key DMEs involved in the APAP metabolism were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we demonstrated that introduction of exogenous hsa-miR-320a, hsa-miR-449a, or hsa-miR-877-5p rescued hepatic cells from APAP-induced hepatotoxicity. Compared to previous studies reporting the gene or miRNA expression profiles associated with APAP-induced hepatotoxicity (Jetten et al 2015; Morishita et al 2006; Wang et al 2009), the present study comprehensively and systematically examined the whole-genome expression of miRNAs and protein-coding genes affected by APAP-induced hepatotoxicity, validated the regulatory network between genes and miRNAs, and thus is relevant to understanding the role of miRNAs in regulating CYP450 expression in development of adaptive tolerance in APAP-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pcdh20, Cldn22, and Rnd1 may participate in cell adhesion, and the genetic variations in this process can cause synaptic dysfunction in PD (Chapman, ). The dysregulations of Psd, Cntnap1, and Capn11 can induce cytoskeletal abnormalities (Garcia‐Fresco et al ., ; Jetten et al ., ; Sironi et al ., ), which is linked to the pathogenesis of PD (Mila et al ., ). Nmbr can regulate the functions of 5‐hydroxytryptamine system (Yamano et al ., ), which may be involved in the development of PD through its interaction with the basal ganglia (Miguelez et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Pcdh20, Cldn22, and Rnd1 may participate in cell adhesion, and the genetic variations in this process can cause synaptic dysfunction in PD (Chapman, 2014). The dysregulations of Psd, Cntnap1, and Capn11 can induce cytoskeletal abnormalities (Garcia-Fresco et al, 2006;Jetten et al, 2015;Figure 3. Pathway analysis of lncRNA/mRNA targets involved in the anti-α-synucleinopathies mechanism of AS.…”
Section: Discussionmentioning
confidence: 99%